Keratinolytic Activity of Artroderma and Chaetomium Species Isolated From Ujjain Soils - Dr Salil Singh (International Journal on Orange Technologies, 2022)
Twelve species of keratin decomposers isolated from 923 samples of feathers, nests and pellets of 90 species of free-living birds were clustered in 4 "econs" (numerical ecological groups): (A) Artroderma tuberculatum, A. ciferrii, A. multifidum, A. cuniculi (associated with the birds nesting in hollows); (B) Arthroderma quadrifidum, (moderately alkalophilic species associated with the birds having a frequent contact with the soil); (C) Aphanoascus fulvescens (D) Arthroderma curreyi, (the species common in water habitats and associated frequently with exoanthropic birds) also isolated from Ujjain soils. Chaetomium is a genus of fungi in the Chaetomiaceae family. It is a dematiaceous (dark-walled) mold normally found in soil, air, cellulose and plant debris. According to the Dictionary of the Fungi (10th edition, 2008), there are about 95 species in the widespread genus. Members of this genus typically have superficial, ostiolar perithecia, covered in hairs. Asci are often clavate and evanescent, bearing eight spores. Ascospores are usually lemon-shaped, commonly colored olive-brown. Mycelia often grows in conglomerate masses that resemble ropes. Chaetomium spp. are also encountered as causative agents of infections in humans. Many cases cause type 1 allergic reactions and infections. A few cases of fatal deep infections due to Chaetomium atrobrunneum have been reported in immunocompromised people. Other clinical syndromes include brain abscess, peritonitis, and onychomycosis. these have also been isolated from Ujjain soils.